Entre a autoridade do monarca e o lugar do poder local: rupturas e continuidades na Assembleia Constituinte de 1823 (Ágora Journal, 2020)
In the present paper, without pretending to exhaust the theme, we analyze some episodes of the Constituent of 1823 with regard to the discussion around the political-administrative spheres in the provinces and municipalities. Our goal is to point out ways to understand how the formations took place, or rather, the reformulations of the municipal and provincial spheres and how they relate to the debate around the authority and the balance of executive (also monarchical) and legislative powers, within of a new monarchical-constitutional arrangement. We observed the existence of a certain discursive and practical continuity, of some elements arising from a non-constitutional state arrangement, without this having meant an antipode to the constitutionalisms of the time, in the formation of the Brazilian state arrangement. In other words, we believe that some stays of the old order were mixed with the changes brought about by the Independence Process and the analysis of the debates that took place in the 1823 Constituent Assembly is fertile to think about these continuities from the old colonial order.